2016
DOI: 10.18632/oncotarget.13401
|View full text |Cite
|
Sign up to set email alerts
|

Digital PCR identifies changes in CDH1 (E-cadherin) transcription pattern in intestinal-type gastric cancer

Abstract: E-cadherin is a cell-cell adhesion protein encoded by CDH1 tumor-suppressor gene. CDH1 inactivating mutations, leading to loss of protein expression, are common in gastric cancer of the diffuse histotype, while alternative mechanisms modulating E-cadherin expression characterize the more common intestinal histotype. These mechanisms are still poorly understood. CDH1 intron 2 has recently emerged as a cis-modulator of E-cadherin expression, encoding non-canonical transcripts. One in particular, CDH1a, proved to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…CDH1 , as a member of the cadherin superfamily, may serve a critical role in apoptotic process and cell-cell adhesion ( 38 ). A previous study demonstrated that CDH1 expression was lower in gastric cancer and this decrease contributed to intestinal-type gastric carcinogenesis ( 39 ). Another study reported that attenuated expression of CDH1 had a key role in tumor invasion and metastasis ( 40 ).…”
Section: Discussionmentioning
confidence: 98%
“…CDH1 , as a member of the cadherin superfamily, may serve a critical role in apoptotic process and cell-cell adhesion ( 38 ). A previous study demonstrated that CDH1 expression was lower in gastric cancer and this decrease contributed to intestinal-type gastric carcinogenesis ( 39 ). Another study reported that attenuated expression of CDH1 had a key role in tumor invasion and metastasis ( 40 ).…”
Section: Discussionmentioning
confidence: 98%
“…dPCR was originally developed for DNA molecular measurements 10,11,12,13 and in time this technology was adapted for the quantification of microRNAs and RNA transcripts 5,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Hold the lid carefully by its side, peel away the protective film, and place the lid with the sticky face up in the correct orientation. 5. Carefully pick up a chip, taking care not to touch the internal part, and load it onto the chip nest in the correct position by pressing down the lever to open the clamp.…”
Section: Chip Preparationmentioning
confidence: 99%
See 2 more Smart Citations